A two-phase approach for the identification of refugees with priority need for mental health care in Lebanon: a validation study. Issue 1 (December 2017) - Llosa, Augusto; Van Ommeren, Mark; Kolappa, Kavitha; Ghantous, Zeina; Souza, Renato; Bastin, Pierre; Slavuckij, Andrej; Grais, Rebecca
Abstract Background Time and resource efficient mental disorder screening mechanisms are not available to identify the growing number of refugees and other forcibly displaced persons in priority need for mental health care. The aim of this study was to identify efficient screening instruments and mechanisms for the detection of moderate and severe mental disorders in a refugee setting. Methods Lay interviewers applied a screening algorithm to detect individuals with severe distress or mental disorders in randomly selected households in a Palestinian refugee camp in Beirut, Lebanon. The method included household informant and individual level interviews using a Vignettes of Local Terms and Concepts for mental disorders (VOLTAC), individual and household informant portions of the field-test version of the WHO-UNHCR Assessment Schedule of Serious Symptoms in Humanitarian Settings (WASSS) and the WHO Self Reporting Questionnaire (SRQ-20). A subset of participants were then reappraised utilizing the Mini International Neuropsychiatric Interview (MINI), WHO Disability Assessment Schedule II, and the Global Assessment of Functioning. The study constitutes a secondary analysis of interview data from 283 randomly selected households (n = 748 adult residents) who participated in a mental health disorders prevalence study in 2010. Results The 5-item household informant portion of WASSS was the most efficient instrument among those tested. It detected adults with severe mental disorders with 95% sensitivity and 71% specificity (Area Under Curve (AUC) = 0.85) and adults with moderate or severe mental disorder with 85.1% sensitivity and 74.8% specificity (AUC = 0.82). The complete screening algorithm demonstrated 100% sensitivity and 58% specificity. Conclusions Our results suggest that a two phase, screen-confirm approach is likely a useful strategy to detect incapacitating mental disorders in humanitarian contexts where mental health specialists are scarce, and that in the context of a multi-step screen confirm mechanism, the household informant portion of field-test version of the WASSS may be an efficient screening tool to identify adults in greatest need for mental health care in humanitarian settings.